2012
DOI: 10.1007/s10554-012-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ECG abnormalities and cardiac parameters in highly trained asymptomatic male endurance athletes: evaluation using cardiac magnetic resonance imaging

Abstract: Intensive endurance training can induce abnormal ECG patterns at rest. These alterations are differentiated into minor, mildly or distinctly abnormal ECG patterns. Echocardiographic data imply a correlation between the extent of these alterations and cardiac parameters like cardiac volume or wall thickness. In comparison to echocardiography, cardiac magnetic resonance imaging (MRI) is characterized by high reproducibility and accuracy. The aim of this study was to investigate the correlation between ECG altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Studies evaluating the clinical impact of long-term intensive endurance training and competition in high-level elite master athletes are rare. [17][18][19][20] In addition, information about training volume (hours per week) and history (years) are often lacking, and cardiopulmonary exercise testing with quantification of the aerobic capacity by measuring maximal oxygen uptake (Vo 2 max) and power output for an assessment of sport-specific performance in professional elite endurance athletes with a long training history have not been performed so far. [17][18][19] Therefore, the aim of this study was to examine the cardiac structure and function with special emphasis on the RV by contrast-enhanced cardiovascular magnetic resonance (CMR) and complementary echocardiographic tissue Doppler imaging and strain data in long-term active, elite endurance master athletes including world class athletes.…”
Section: May 17 2016mentioning
confidence: 99%
“…Studies evaluating the clinical impact of long-term intensive endurance training and competition in high-level elite master athletes are rare. [17][18][19][20] In addition, information about training volume (hours per week) and history (years) are often lacking, and cardiopulmonary exercise testing with quantification of the aerobic capacity by measuring maximal oxygen uptake (Vo 2 max) and power output for an assessment of sport-specific performance in professional elite endurance athletes with a long training history have not been performed so far. [17][18][19] Therefore, the aim of this study was to examine the cardiac structure and function with special emphasis on the RV by contrast-enhanced cardiovascular magnetic resonance (CMR) and complementary echocardiographic tissue Doppler imaging and strain data in long-term active, elite endurance master athletes including world class athletes.…”
Section: May 17 2016mentioning
confidence: 99%
“…Even left atrial volume index has been shown and used as an important prognosticator, for example in dialysis patients (Ozdogan et al, 2010). A more recent interest has developed in sports medicine for comparison of different types of training and athletes regarding cardiac and left ventricular performance assessed by normalized cardiac output and left ventricular volumes (Erz et al, 2013). But obviously, the normalization may be complicated by extreme BSA values in this population, as recently discussed in a study on cardiac morbidity in obese patients (Adler et al, 2013), where the authors conclude that 'cardiac and stroke indices can be misleading relative to the underlying raw values as a result of distortion by widely used BSA formulae'.…”
Section: Clinical Impact Of Bsa Calculationsmentioning
confidence: 99%
“…3 It is generally accepted that exercise benefits cardiovascular health, 4 but myocardial fibrosis (MF) has been detected in endurance athletes by cardiac magnetic resonance imaging (CMR) using late gadolinium enhancement (LGE). [5][6][7][8][9][10][11] Myocardial fibrosis is defined by a significant increase in the collagen volume of myocardial tissue. It is a complex process that involves all components of the myocardial tissue and can be triggered by tissue injury from myocardial ischemia (hypoxia), inflammation, and hypertensive overload.…”
mentioning
confidence: 99%